Linking local rice processors’ access to rural radio, gender, and livelihoods in Benin - Zossou, Espérance; VODOUHE, DAVO SIMPLICE; Van Mele, Paul; Agboh-Noameshie, Afiavi Rita; Lebailly, Philippe (My University, 2015)
In a context of low literacy rates and a high level of rurality, the use of rural radio in agricultural extension is a method that can bridge the gap that exists between researchers, extension workers, and farmers. This article examines the level of farmers’ access to rural radio in relation to gender and livelihoods. The study was conducted in Benin with 18 rural radio stations and 240 rice processors, using the sustainable livelihoods framework to examine the relationship between access to rural radio and livelihoods. Although the study cannot draw conclusions on causal relationships, rice processors who often listened to agricultural broadcasts had better social, financial, and human capital stocks compared to those who did not. Despite the efforts of 72% of the radio stations to link up with extension services, half of the rice processors rarely or never listened to agricultural broadcasts, because the timing of the broadcasts was inappropriate. Interactive radio sessions with farmers that involve government officials will need to address this if they are to become more effective.
Keywords: Technology – Media; Gender and diversity; Environment (built and natural) –; Agriculture; Sub-Saharan Africa; Introduction